Electrochemical Determination of Trichloroacetic Acid using Platinum Electrode - Khodari, M.; Abd-Elrady, A. A.; Rabie, E.M.; Assaf, H.F. (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
The electrochemical reduction of Trichloroacetic acid (TCA) on a platinum electrode by cyclic and linear sweep voltammetry was described. The measurements were investigated under optimized conditions. The supporting electrolyte was 0.01 M sodiumnitrate solution (pH 6.0), scan rate 50mV\s and the reached detection and quantification limits was 4x10-6 mol l-1. The obtained result indicated linear increasing of the current with concentration of TCAA between lower and upper detection limits and excellent sensitivity towards TCAA reduction, which demonstrates the analytical utility of platinum electrode. Meanwhile, interference from other ions and substances were examined. The experimental results indicate that the method for the determination of TCAA samples is successful comparing with other methods or techniques.